Mobile executions of Slow DoS Attacks. (16th October 2015) - Cambiaso, Enrico; Papaleo, Gianluca; Chiola, Giovanni; Aiello, Maurizio
Abstract : Denial of Service attacks are executed to prevent the access to an Internet service by legitimate users. Recently, such attacks evolved to the so called Slow DoS attacks, which are able to reach their goal by using tiny amounts of network bandwidth. In this article we focus on such category of threats: we design an innovative offensive tool, SlowDroid, that may affect multiple protocols requiring minimal resources to the attacker. In virtue of this, the attack can even be executed from a mobile device. We compare the attack with similar already existing tools, measuring the results obtained based on new metrics we introduce, proving that the proposed threat represents a serious menace.